Sosialisasi Pengembangan Ekspor Melalui International E-Commerce di Kampung Batik Laweyan Solo - Damayanti, Christy; Murdani, Andika Drajat (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2019)
The e-commerce market trend is taking place around the world. This trend encourages international trade be more intense. This can be an opportunity for Indonesia to be able to develop its exports rate using e-commerce. Based on this background, this program purposes to provide indeep information to industry and trade players about how to increase their potential and expand the market through international e-commerce. This international e-commerce should be a solution to improve its economic welfare. The method of this program is carried out through assessment and socialization at the location of service, as Kampung Batik Laweyan Solo. Exploration activities were to obtain detailed information about program targets, which are held in August and September 2018. Furthermore, a one-day socialization event is held on 28 October 2018. The results of this program are (1) business actors can obtain information about the potential export by utilizing international e-commerce; (2) for the region, can develop regional potential, regional promotion, and regional economic development; (3) for universities, as a fulfillment of the Tri Dharma elements of Higher Education.Keywords : export, international e-commerce, Kampung Batik LaweyanI. PENDAHULUAN